Dampak Rasio Guru terhadap Prestasi Belajar Siswa di RA Yaspi Muneng 2 - Salsabila, Ervina; Kesuma, Yonanda Meisya; Astuti, Winni; Panuti, Putri Rahayuning (JURNAL INDRIA (Jurnal Ilmiah Pendidikan Prasekolah dan Sekolah Awal), 2025)
Early childhood education is the main foundation for children to develop in the future. Optimal interaction with the learning environment is essential to support overall growth and development. One crucial factor in supporting this process is the ratio between educators and students. This study aims to investigate the impact of the teacher-student ratio on student academic performance at RA Yaspi Muneng 2. The research approach used is qualitative descriptive with a case study method. Data collection techniques include classroom observation, in-depth interviews with teachers and parents, and documentation of student learning outcomes. The research findings indicate that a single teacher guiding two age groups in one classroom faces difficulties in providing individual attention, limitations in evaluating student progress, and administrative challenges. Interviews with parents also revealed that students' development differs from that of their siblings attending different schools, with parents citing the limited number of educators as a contributing factor. An unfavorable teacher-student ratio significantly impacts the effectiveness of learning and student academic performance.